A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia - Sparks, John S.; Rush, Leila M.r. (Zootaxa, 2005)
Bedotia albomarginata, a new species of Malagasy rainbowfish, is described from forested habitats in the southeastern highlands of Madagascar. The new species is distinguished from congeners by the presence of broad white margins on the second dorsal fin and anal fin in males, a markedly lanceolate caudal fin in adult males, and in life, by a bright yellow to orangish-red anal fin in both sexes. Bedotia albomarginata is known only from small streams and swamps within the upper to middle reaches of the Mananara and Rienana river drainage basins.